(untitled) (Research, Society and Development, 2020)
This study aimed to investigate the contributions of Wanda Horta’s Theory of Basic Human Needs to nursing care during pregnancy based on scientific productions. Integrative review conducted on the Web of Science databases; Scopus; CINAHL; LILACS; MEDLINE / PUBMED and VHL with the “Nursing Care AND Nursing Theory AND Pregnancy” and “Nursing Care AND Nursing Theory AND Pregnant Womam” combinations between January and February 2019, including articles available electronically in full, without language restriction and without clipping temporal. We found 1726 articles, 104 were pre-selected and 06 met the inclusion criteria and composed the sample. The results were discussed in two categories: Contributions of the Basic Human Needs Theory to Professional Practice and Contributions of the Basic Human Needs Theory to Pregnant Women. It was evidenced that the use of the theory enhances the visibility of nurses’ work, subsidizes individualized nursing care and improves professional records. It is also emphasized that the theory makes it possible to recognize the profile of pregnant women, elaborate an individualized care plan and privileges interpersonal relationships. It was concluded that this theory allows recognition and attendance to the demands presented by pregnant women and solidifies nursing’s own knowledge.